IDENTIFIKASI MISKONSEPSI SISWA PADA KONSEP FOTOSINTESIS DAN RESPIRASI TUMBUHAN - Kartika Fandiyani; Tri Jalmo; Rini Rita T. Marpaung (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2017)
This research aim was to describe students' misconception in the concept of plants photosynthesis and respiration and all factors that affected students' misconception. This research used descriptive design. The Samples were 351 SMP students of VIII grade at Tumijajar district academic year 2015/2016 which were chosen by using purposive sampling technique. Data were collected by multiple choicetest and student questionnaire. The test result were analyzed using the CRI, while the student questionnaire were analyzed using Pearson correlation test. The result of data analysis showed that students get misconception that was 57,30% with "adequate" criteria. The misconception was commonly on respiration concept with the "high" criteria (62,10%). Pearson correlation test results showed that the factors correlated to students' misconceptions that was motivation factor. There are only 16,24% students who have learned about plant photosynthesis and respiration concept on their home before learning with teacher of the school. Penelitian ini bertujuan mengetahui gambaran miskonsepsi siswa pada konsep fotosintesis dan respirasi tumbuhan, serta faktor yang berpengaruh terhadap miskonsepsi siswa. Desain penelitian dengan desain penelitian deskriptif. Sampel terdiri atas 351 siswa kelas VIII SMP se- Kecamatan Tumijajar pada tahun ajaran 2015/2016 yang dipilih dengan menggunakan teknik purposive sampling. Pengumpulan data menggunakan tes CRI dan angket siswa. Hasil analisisdata menunjukkan rerata miskonsepsi siswa kelas VIII se-kecamatan tumijajar sebesar 57,30% dengan kriteria sedang. Miskonsepsi paling sering terjadi pada konsep respirasi dengan kriteria tinggi (62,10%). Hasil uji korelasi pearson angket siswa menunjukkan faktor yang berkorelasi terhadap miskonsepsi siswa yaitu faktor motivasi siswa. Hasil angket menunjukkan hanya sebesar 16,24% siswa yang belajar konsep fotosintesis dan respirasi tumbuhan dirumah sebelum belajar bersama guru disekolah.Kata kunci : CRI, faktor miskonsepsi, fotosintesis, miskonsepsi, respirasi